2017
DOI: 10.1186/s40497-017-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic entrepreneurs and online home-based businesses: an exploratory study

Abstract: This exploratory, qualitative study considers how online home-based businesses offer opportunities for ethnic entrepreneurs to 'break out' of traditional highly competitive and low margin sectors. Previous studies have found a positive association between ethnic minorities' high levels of entrepreneurship and home computer use in ethnic groups. Despite these associations, previous studies have overlooked the particular opportunities offered by home-based online businesses to ethnic entrepreneurs. The study ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 69 publications
0
32
0
1
Order By: Relevance
“…The embeddedness framework recognises that the entrepreneur is both socially and economically located in an ethnic community (Katila and Wahlbeck, 2012) in addition to the wider social, economic and institutional context of the host country. Importantly, changes over time in the wider institutional and economic environment open up new business opportunities for entrepreneurs able to access the requisite sets of resources (Anwar and Daniel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The embeddedness framework recognises that the entrepreneur is both socially and economically located in an ethnic community (Katila and Wahlbeck, 2012) in addition to the wider social, economic and institutional context of the host country. Importantly, changes over time in the wider institutional and economic environment open up new business opportunities for entrepreneurs able to access the requisite sets of resources (Anwar and Daniel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies based on the theory have tended to overlook entrepreneurial agency, suggesting that EMEs have little influence over their context. In contrast, Anwar and Daniel (2017) have shown that EMEs creatively influence the varied forces acting on them, suggesting a more mutually constitutive relationship.…”
Section: Prior Literature: Emes and Break Outmentioning
confidence: 89%
“…Increases in female EMEs may be considered as an outcome of their mixed embeddedness. Drawing on the notion of agency and recursive change (Anwar and Daniel, 2017), increased rates of female EMEs could influence normative or 1423 Contemporary ethnic minority entrepreneurship mimetic forces in the local or national context, encouraging further female EMEs, for example through role modelling, mentoring or business support policies targeted at female entrepreneurs and female EMEs (Langevang et al, 2015).…”
Section: H Less Per Week Increased Weekly Earningsmentioning
confidence: 99%
“…Home-based businesses more specifically frequently use sub-contracting for more difficult or time-consuming IT tasks (Anwar and Daniel, 2017). Sub-contracting seems also to be preferred over hiring employees as a way to maintain a home location and flexibility (Ekinsmyth, 2014;van Gelderen et al, 2008).…”
Section: Business Networkmentioning
confidence: 99%
“…In a comparative study of home-based businesses and small businesses in commercial premises in Scotland, no home-based business had accessed public sector grants and loans . Moreover, difficulties with securing bank loans due to the home-based nature of the business were mentioned by ethnic home-based entrepreneurs in the UK that operate online businesses (Anwar and Daniel, 2017).…”
Section: Access To Loans and Public-sector Finance Programmesmentioning
confidence: 99%